2022
DOI: 10.1002/jmor.21506
|View full text |Cite
|
Sign up to set email alerts
|

A morphological analysis of carnivoran ossicles from Rancho La Brea

Abstract: The morphology of the mammalian middle ear-including the size, shape, and stiffness of individual ossicles-controls their vibrational response to sound and, is closely related to an animal's auditory capabilities. While the relationship between middle ear morphology and hearing frequency has been explored in living carnivorans, the size and shape of ossicles in fossil carnivorans have been sparsely documented. In this study, we present the first morphological data on four iconic carnivoran taxa from the Rancho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…A recent analysis of ossicular size in fossil and extant carnivorans (Dickinson et al, 2022) also reported similar trends in both canids (geometric mean vs. body mass: malleus, slope = 0.29, r 2 = .63; incus, slope = 0.37, r 2 = .84; stapes, slope = 0.59, r 2 = .24) and felids (malleus, slope = 0.49, r 2 = .90; incus, slope = 0.53, r 2 = .96; stapes, slope = 0.40, r 2 = .91). Finally, a cross‐mammalian analysis of ossicle mass relative to skull mass in 63 species (Nummela, 1995) reported a negatively allometric relationship of similar magnitude (slope = 0.51, r 2 = .90).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent analysis of ossicular size in fossil and extant carnivorans (Dickinson et al, 2022) also reported similar trends in both canids (geometric mean vs. body mass: malleus, slope = 0.29, r 2 = .63; incus, slope = 0.37, r 2 = .84; stapes, slope = 0.59, r 2 = .24) and felids (malleus, slope = 0.49, r 2 = .90; incus, slope = 0.53, r 2 = .96; stapes, slope = 0.40, r 2 = .91). Finally, a cross‐mammalian analysis of ossicle mass relative to skull mass in 63 species (Nummela, 1995) reported a negatively allometric relationship of similar magnitude (slope = 0.51, r 2 = .90).…”
Section: Discussionmentioning
confidence: 99%
“…In the same sample, combined incus + malleus mass (slope = 0.477; r 2 = .864) and stapes mass (slope = 0.510, r 2 = .876) exhibit similar slopes to our own observations of incus (slope = 0.343, r 2 = .437), malleus (slope = 0.295, r 2 = .415) and stapes (slope = 0.521, r 2 = .595) volume scaling in phyllostomids (Table 5), though it should be noted that these previously published data were not analyzed with phylogenetic adjustments and thus not directly comparable to our own results. A recent analysis of ossicular size in fossil and extant carnivorans (Dickinson et al, 2022) also reported similar trends in both canids (geometric mean vs. body mass: malleus, slope = 0.29, r 2 = .63; incus, slope = 0.37, r 2 = .84; stapes, slope = 0.59, r 2 = .24) and felids (malleus, slope = 0.49, r 2 = .90; incus, slope = 0.53, r 2 = .96; stapes, slope = 0.40, r 2 = .91). Finally, a cross-mammalian analysis of ossicle mass relative to skull mass in 63 species (Nummela, 1995) reported a negatively allometric relationship of similar magnitude (slope = 0.51, r 2 = .90).…”
Section: Scaling Of the Ossicular Chain In Bats And Other Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…While early excavations at the site primarily recovered large fossil bones, particularly craniodental material and limb bones, more recent excavations have produced large collections of well‐preserved smaller fossils (Shaw, 1982). The quantity and quality of preservation provide a unique opportunity for the quantitative examination of the functional morphology of small fossils, including clavicles (Hartstone‐Rose et al, 2012), bacula (Hartstone‐Rose et al, 2015), canid hyoids (Flores et al, 2020), and auditory ossicles (Dickinson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%